Novel HCN1 Mutations Associated With Epilepsy and Impacts on Neuronal Excitability - Xie, Changning; Liu, Fangyun; He, Hailan; He, Fang; Mao, Leilei; Wang, Xiaole; Yin, Fei; Peng, Jing (Frontiers in Molecular Neuroscience, 2022)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channel plays critical roles in regulating the resting membrane potential and integrating synaptic transmission. Variants in HCN1 were recognized as causes of epilepsy, and mutant HCN1channels could act loss-of-function (LOF), loss- and gain-of-function and gain-of-function mechanisms. We identified two pathogenic variants (I380F, S710Rfs*71), two likely pathogenic (E240G, A395G) and one paternal inherited variant of uncertain significance (V572A). Four variants were never reported in previous studies. Electrophysiological experiments showed five variants impaired the biophysical properties of HCN1 channels, including current densities, activation/deactivation kinetics. Moreover, we observed three variants affected biophysical properties of WT HCN1 channels in heterozygous conditions. Immunofluorescent experiments showed two variants reduced the protein expression of HCN1 in neurons. Neurons expressing HCN1 E240G (GOF) channels showed increased input resistance. However, neurons expressing HCN1 I380F (LOF) channels showed increased firing rate of action potentials, thus led to neuronal hyperexcitability. In conclusion, the present study expands the genotypic and phenotypic spectrum of patients with HCN1-related epilepsy and clarify underlying mechanisms. We reported five new cases including four unreported likely/pathogenic variants. We provided assessments of biophysical function for each variant, which may help patients to receive individual therapy in the future. We confirmed that HCN1 variants contributed to neural hyperexcitability by regulating input resistance and firing rate of action potentials and for the first time they affected protein expression in neurons.